Effects of Increasing Crystalline Amino Acids in Sorghum- or Corn-based Diets on Finishing Pig Growth Performance and Carcass Composition - K. E. Jordan; R. D. Goodband; J. C. Woodworth; M. D. Tokach; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2015)
A study was conducted to determine the impact of increasing crystalline amino acids in either sorghum- or corn-based diets on finishing pig growth and carcass composition. A total of 288 pigs (PIC 327×1050; initially 101.1 lb) were used in a 90-d study with 8 pigs per pen and 6 pens per treatment. Treatments were arranged in a 2 × 3 factorial with main effects of grain source (sorghum vs. corn) and crystalline AA supplementation (low, medium, or high). Amino acids ratios to Lys as well as standardized ileal digestibility coefficients used were set by NRC (2012). All diets were formulated to the same Lys:NE ratio and at 95% of the pig’s estimated Lys requirement to ensure that AA were not above the pigs’ requirement. The grain sources and soybean meal were analyzed for AA profile and diets formulated from these concentrations. The low AA fortification contained L-lysine HCl and DL-methionine. The medium AA fortification contained L-lysine HCl, DL-methionine, and L-threonine. The high AA fortification contained L-lysine HCl, DL-methionine, L-threonine, and L-valine in sorghumor L-tryptophan in corn-based diets. Overall, there were no grain source × crystalline AA level interactions observed for any response criteria measured. Pigs fed corn-based diets tended to have greater ADG (P<0.072) and had better F/G (P<0.01) than those fed sorghum-based diets. As crystalline AA increased, ADG tended to increase then decrease (quadratic; P=0.057), and ADFI decreased (linear; P = 0.019) resulting in a tendency for improved F/G (quadratic; P=0.097). Pigs fed sorghum had decreased (P<0.01) jowl fat iodine value in comparison to those fed corn-based diets. Crystalline AA level did not impact carcass characteristics. In conclusion, diets with high AA fortification had decreased ADG and ADFI with slightly improved F/G compared with low or medium AA fortification. Furthermore, grain sorghum had approximately 97% of the feeding value relative to corn based on F/G.
Keywords: corn; crystalline AA; finishing pig; sorghum